Decellularized extracellular matrix for bioengineering physiomimetic 3D in Vitro Tumor Models - Ferreira, Luís P. (2022)
Recent advances in the extraction and purification of decellularized extracellular matrix (dECM) obtained from healthy or malignant tissues open new avenues for engineering physiomimetic 3D in vitro tumor models, which closely recapitulate key biomolecular hallmarks and the dynamic cancer cell-ECM interactions in the tumor microenvironment. We review current and upcoming methodologies for chemical modification of dECM-based biomaterials and advanced bioprocessing into organotypic 3D solid tumor models. A comprehensive review of disruptive advances and shortcomings of exploring dECM-based biomaterials for recapitulating the native tumor-supporting matrix is also provided. We hope to drive the discussion on how 3D dECM testing platforms can be leveraged for generating microphysiological tumor surrogates that generate more robust and predictive data on therapeutic bioperformance.